Questioning the narrative: stories from a community learning centre in the Western Cape - Loizides, Jessica (School of Education, 2025)
In 2013, the Department of Higher Education and Training released a new vision for South Africa's postschool education sector. Part of this vision was the creation of a new kind of institution: the Community Education and Training College (CETC). These colleges consolidated the public adult education system into nine provincial CETCs, each with several community learning centres (CLCs). The goal – community-based learning offering a diversity of programmes that respond to local needs, facilitate access to occupational training, while also providing ways for adults to complete formal schooling. Several years on, this study explores the stories of four educators from one CLC in theWestern Cape in relation to the promises and proposals put forward by this new system. Through one-on-one semi-structured interviews, applying a constructionist narrative approach, the project considers how educator narratives reflect, complicate and reject dominant narratives about the roles and purposes of education through their experiences at this CLC. A review of the literature and policies informing the CETC system, including the proposed GETCA and NASCA qualifications, shows that despite claims for a more responsive and localised focus, it continues to emphasise top-down approaches to curricula and testing, while often portraying a deficit view of educators, their knowledge and skills. In contrast, educator narratives provide a deeper understanding of how they work within restrictive curricular structures to perform relational care and knowledge work, with in-depth knowledge of who the CLC students are and their needs. These narratives also assist us in shaping a vision for community learning, engagement, healing and collective solidarity beyond the often vague and symbolic discursive work of policy.